Ownership Structure, Business Links and Perfor-mance of Firms in a Transforming Economy The Case of Hungary - Janos Toth Istvan (Hungarian Academy of Sciences, Institute of Economics, 1999)
This study concentrates on the analysis of the characteristics of the ownership and business links existing between the enterprises; the effects of business links and financial discipline on the effectiveness and growth capability of enterprises, as well as the changes which have taken place since 1992 in the performance of Hungarian enterprises. The author regard financial discipline (the breach of payment obligations toward the partners or in the delayed payment of taxes) a very important indicator in that how safe the business links of a company can be considered. The results show that the occurrence of liquidity problems in itself has a significant effect on the breach of financial discipline. The absence of firms growth increases the chance for breach of financial discipline and the foreign-owned companies are better protected against the looser payment discipline of the partners. The results also confirm the better growth capability of foreign companies. If companies which are related by ownership links also establish business links, then the closer business links make better growth dynamics probable. Companies, which are each others' suppliers within a company group usually, achieve a faster growth than the rest of the companies. The analysis of tax returns shows that we are not talking simply of the temporary good influence of the transition from state-ownership to private ownership but we can emphasize a certain type of private ownership, that is, foreign ownership, which significantly improves the performance of the companies. According to the results, the contributions to the value added do not show a positive effect of privatization. The better performance of privatized (between 19931996) companies measured by the value added to employment in 1996 is not the result of privatization, but other technological, organizational influences or business conditions, which were in effect even before privatization.
Keywords: 330